ERRORS AND MISTAKES FOUND IN NON- ENGLISH STUDY PROGRAM STUDENTS WRITING PRODUCTS - Sijono Sijono; Ilinawati Ilinawati (Journal of English Educational Study (JEES), 2020)
This study focuses on students' errors that occur when asked to write simple present tense to non-English English study program students at a private university in the border area of West Kalimantan. Researchers conducted this research to get an overview of the causes of students making mistakes and errors in writing simple present tense.In analyzing the data, the researchers used qualitative research design to describe the various forms of errors or mistakes students when writing simple present tense. The data analysis in this study was taken from 120 Non-English Study program students.The researchers applied purposive sampling to determine the research subject.Based on the number of sampling of the research, the researchers analyzed 120 worksheets of the students translation task.Researchers found a total of 395 cases. The findings showed that all cases described in this study were categorized as errors. The researchers found that students failed to carry out their knowledge of the simple present tense.The most common errors found in this study, such as the rule of adding extra 's / es', the rule of using 'Tobe' and errors arising from the addition of 'Ving' can be minimized with regular writing practice. Keywords : Errors, Mistakes, Students  writing Products